2021
DOI: 10.3390/cells10010060
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Death in the CNS Autonomic Control Center Comes Very Early after Cardiac Arrest and Is Not Significantly Attenuated by Prompt Hypothermic Treatment in Rats

Abstract: Autonomic dysfunction in the central nervous system (CNS) can cause death after recovery from a cardiac arrest (CA). However, few studies on histopathological changes in animal models of CA have been reported. In this study, we investigated the prevalence of neuronal death and damage in various brain regions and the spinal cord at early times after asphyxial CA and we studied the relationship between the mortality rate and neuronal damage following hypothermic treatment after CA. Rats were subjected to 7–8 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In a rat model of ACA/CPR, neuronal death (loss) in the anterior horn in the lumbar part of the spinal cord occurs at one day after ACA/CPR [9]. In addition, Ahn et al [10] recently reported that neuronal death in the central nervous system (CNS) autonomic control center (myelencephalon and thoracolumbar division of the spinal cord) occurred very early compared to the other CNS divisions after ACA/CPR in rats. In our current study, we found that ventral motor neurons at the level of the lumbar spinal cord were dead at two days after ACA/CPR in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model of ACA/CPR, neuronal death (loss) in the anterior horn in the lumbar part of the spinal cord occurs at one day after ACA/CPR [9]. In addition, Ahn et al [10] recently reported that neuronal death in the central nervous system (CNS) autonomic control center (myelencephalon and thoracolumbar division of the spinal cord) occurred very early compared to the other CNS divisions after ACA/CPR in rats. In our current study, we found that ventral motor neurons at the level of the lumbar spinal cord were dead at two days after ACA/CPR in rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CA is one of the causes of severe spinal cord injuries including paraplegia, which negatively affects the quality of life in patients [5][6][7]. It is well known that motor neurons located in the ventral horn of the spinal cord are very vulnerable to ischemia-reperfusion injury [8][9][10]. However, the factors protecting or attenuating the damage of spinal motor neurons following ischemic insults have been insufficiently reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…ACA induced according to the published protocols [ 45 , 46 ]. In brief, rats were anesthetized with 2.5% isoflurane in oxygen (33%) and nitrous oxide (67%), and the rats were endotracheally intubated with cannula (14-gauge) and maintained to ventilate respiration using a rodent ventilator (Harvard Apparatus, Holliston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CPR was performed according to the published protocols [ 45 , 46 ]. In brief, CPR was performed from 5 min after ACA as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation